2006
DOI: 10.1007/s10562-006-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Potassium Doping on the Activity and the Sulfur Poisoning Resistance of Soot Oxidation Catalysts

Abstract: Soot oxidation on potassium nitrate impregnated cerium oxide and manganese cerium mixed oxide was investigated using TG-FTIR. It was found, that potassium nitrate promotes the soot oxidation by enhancing the contact between the soot and the catalyst, as soot ignition temperature corresponds to the melting point of potassium nitrate for both the individual and the mixed oxide. Since potassium nitrate is easier sulfatized than cerium or manganese, the susceptibility of the catalyst to sulfur poisoning is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…To accomplish soot oxidation at lower temperatures, various catalysts were developed [3][4][5][6][7][8][9]. Therein, potassium-containing materials show considerable activity and the relevant mechanisms have been suggested in many studies [10][11][12][13][14][15][16][17][18]. Besides, catalytic soot oxidation is affected by the composition of the reaction gas (O 2 and/ or NO x ).…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish soot oxidation at lower temperatures, various catalysts were developed [3][4][5][6][7][8][9]. Therein, potassium-containing materials show considerable activity and the relevant mechanisms have been suggested in many studies [10][11][12][13][14][15][16][17][18]. Besides, catalytic soot oxidation is affected by the composition of the reaction gas (O 2 and/ or NO x ).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, extensive investigations on potassium-promoted catalysts for soot combustion [14][15][16][17], as well as NOx adsorbers [18], have been performed. Querini et al reported that the Co, K/MgO catalysts are very active for soot combustion due to their improvement in surface mobility and/or volatility in the presence of potassium [19].…”
Section: Introductionmentioning
confidence: 99%
“…K also promotes the stability of the catalyst. It is found that the sulfur resistance of the MnO x -CeO 2 and Cu/CeO 2 catalyst is improved by impregnating KNO 3 [117,129], which is attributed to the protection of the active center by the basicity of K. The addition of K to the CaO-MgO catalyst reduces the content and stability of carbonates formed on the surface, while the carbonate groups invalidate the active sites and prevent the adsorption and dissociation of O 2 [116]. K reduces decomposition temperatures of carbonate on catalyst surfaces is also found [130].…”
Section: Promotion Effects Of K On Catalyst Propertiesmentioning
confidence: 99%